Applications for mobile devices in Chemical education: a research in foreign literature (Research, Society and Development, 2020)
We present here a research in the light of a “State of the Art” on the use of mobile apps in the teaching of Chemistry, in the database Eric - Education Resources Information Center, period from 2010 to 2019, using the descriptors “App”, “Chemistry Education”and“High School”. The research corpus consists of seven publications in the Journal of Chemical Education that emerged from the database. The main objective of the study was to map which applications have been used in foreign research involving the teaching of chemistry, especially aimed at high school. It was evident that the applications presented can enable the Chemistry teacher to develop a series of activities, inside and outside the classroom, in order to qualify the teaching-learning process. However, attention is drawn to the inexpressive amount of work that uses applications in the Teaching of Chemistry, with an experimental bias.